Unlocking Sacred Landscapes Religious and Insular Identities in Context - Papantoniou, Giorgos; Vionis, Athanasios K.; Morris, Christine E. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is the third and final volume in a trilogy of collective peer-reviewed works of the Unlocking Sacred Landscapes research network. It encompasses various approaches both to ritual space and to artefacts relating to ritual practice and cults involving islandscapes (including landscapes and seascapes). The terms ritual and cult are used broadly to include sanctuaries, temples, and churches, as well as the domestic and funerary spheres of life. Although the main focus of the Special Issue is the Mediterranean region, studies related to other regions are included to stimulate wider methodological dialogues and comparative approaches. The time span ranges from prehistory to the recent past, and research includes ethnography and cultural heritage studies. The contributions of the issue deal with historical and culturally driven perspectives that recognise the complexities of island religious systems as well as the active role of the islanders in constructing their own religious identities, irrespective of emulation and acculturation. The authors consider inter-island and island/mainland relations, maritime connectivity of things and people, and ideological values in relation to religious change, as well as the relation between island space and environment in the performance and maintenance of spiritual lives.